Relation of a Socioeconomic Index with Cognitive Function and Neuroimaging in Hypertensive Individuals - Paradela, Regina Silva; Ferreira, Naomi Vidal; Nucci, Mariana Penteado; Cabella, Brenno [UNESP]; Martino, Luiza Menoni; Torres, Laura Aló; Costa, Danielle Irigoyen Da; Consolim-Colombo, Fernanda Marciano; Suemoto, Claudia Kimie; Irigoyen, Maria Claudia (SAGE Publications, 2021)
Background: Socioeconomic factors are important contributors to brain health. However, data from developing countries (where social inequalities are the most prominent) are still scarce, particularly about hypertensive individuals. Objective: To evaluate the relationship between socioeconomic index, cognitive function, and cortical brain volume, as well as determine whether white matter hyperintensities are mediators of the association of the socioeconomic index with cognitive function in hypertensive individuals. Methods: We assessed 92 hypertensive participants (mean age = 58±8.6 years, 65.2%female). Cognitive evaluation and neuroimaging were performed and clinical and sociodemographic data were collected using questionnaires. A socioeconomic index was created using education, income, occupation (manual or non-manual work), and race. The associations of the socioeconomic index with cognitive performance and brain volume were investigated using linear regression models adjusted for age, sex, time of hypertension since diagnosis, and comorbidities. A causal mediation analysis was also conducted. Results: Better socioeconomic status was associated with better visuospatial ability, executive function, and global cognition. We found associations between a better socioeconomic index and a higher parietal lobe volume. White matter hyperintensities were also not mediators in the relationship between the socioeconomic index and cognitive performance. Conclusion: Socioeconomic disadvantages are associated with worse cognitive performance and brain volume in individuals with hypertension.
Keywords: Brain volume; Cognitive dysfunction; Executive function; Hypertension; Neuroimaging; Social determinants of health; White matter hyperintensities